2021
DOI: 10.1002/jor.25107
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of bone microarchitecture and matrix composition to implant fixation strength in rats

Abstract: Bone microarchitectural parameters significantly contribute to implant fixation strength but the role of bone matrix composition is not well understood. To determine the relative contribution of microarchitecture and bone matrix composition to implant fixation strength, we placed titanium implants in 12‐week‐old intact Sprague–Dawley rats, ovariectomized‐Sprague–Dawley rats, and Zucker diabetic fatty rats. We assessed bone microarchitecture by microcomputed tomography, bone matrix composition by Raman spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…We have previously used this intramedullary rat model to evaluate the skeletal response to implant placement, (31) the pathogenesis of particle-induced loss of implant fixation strength, (48,49) and the efficacy of various anabolic treatments to promote implant osseointegration. (50)(51)(52) Similar to our previous study using the Zucker Diabetic Fatty rat model of T2DM, (13) we found no differences in osseointegration at 2 weeks post-implantation. Unlike the ZDF model, the current study did not find a significant difference in osseointegration 10 weeks post-implant placement.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…We have previously used this intramedullary rat model to evaluate the skeletal response to implant placement, (31) the pathogenesis of particle-induced loss of implant fixation strength, (48,49) and the efficacy of various anabolic treatments to promote implant osseointegration. (50)(51)(52) Similar to our previous study using the Zucker Diabetic Fatty rat model of T2DM, (13) we found no differences in osseointegration at 2 weeks post-implantation. Unlike the ZDF model, the current study did not find a significant difference in osseointegration 10 weeks post-implant placement.…”
Section: Discussionsupporting
confidence: 87%
“…After implant placement, animals were then randomly divided into two groups for postsurgical euthanization: 2 weeks and 10 weeks. The postsurgical time points were selected based on our previous study with the ZDF rat, ( 13 ) which showed increasing osseointegration and fixation strength in these two time points, and a study describing the longitudinal remodeling rates after intramedullary implant placement in the rat model that noted gradually increasing bone formation and resorption rates from implant placement to 8‐week postsurgery and a trend toward declining rates at 12‐week postsurgical placement. ( 31 ) The anticipated sample size of 8 per group was selected based on prior experiments demonstrating significant differences in the fixation strength between Sprague Dawley and ZDF.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations